Pemanfaatan zeolit alam sebagai adsorben logam berat dalam air limbah industri - zumaroh, ziya datun (Maliki Interdisciplinary Journal, 2025)
This study aims to explore the potential and effectiveness of natural zeolite as an adsorbent for heavy metals in industrial wastewater treatment. This topic is crucial, as heavy metal contamination from industrial waste poses serious risks to the environment and human health. The article adopts a literature review method by analyzing five national and international journals relevant to the topic. Each journal is evaluated based on content related to zeolite characteristics, adsorption mechanisms, types of heavy metals, activation methods, and real-world applications. The data are described narratively and presented in tables. The review shows that zeolite has a high capacity to adsorb heavy metals such as lead, chromium, and iron, making it a promising and eco-friendly solution for industrial wastewater management.